Perceptions of Teachers and Student on the Utilization of Artificial intelligence in Accounting Education: A Case Study at SMKN 1 Boyolali - Ahadi, Ahadi; Jatmika, Surya (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
This study explores the perceptions of accounting teachers and students at SMKN 1 Boyolali on the integration of Artificial Intelligence (AI) in accounting education. Using a qualitative case study approach, data was gathered through interviews and document review, with validity ensured through source triangulation. The findings reveal that both teachers and students view AI positively. Teachers recognize AI's potential to personalize learning and provide instant feedback, with ChatGPT being the preferred tool due to its ease of use. However, challenges such as limited facilities and poor internet connectivity hinder effective implementation. Teachers highlight the need for more advanced AI tools and specific training to enhance their technological skills. Similarly, students appreciate AI's role in deepening understanding of accounting concepts, accessing information efficiently, and receiving timely feedback, which contributes to better learning outcomes. Yet, they also face obstacles related to infrastructure and internet access. Despite these limitations, both groups agree that AI holds significant transformative potential in vocational education. They advocate for improved infrastructure, advanced AI development, and targeted training to optimize AI integration in teaching and learning. The study concludes that AI can significantly enhance the quality of accounting education by improving access to resources and supporting more effective teaching and learning experiences.